Simultaneous Stenting for Symptomatic Tandem Extracranial and Intracranial Posterior Circulation Stenoses: Long-Term Outcomes and Procedural Experience - Jia, Zichang; Zhao, Yanqing; Wang, Peng; Han, Jintao; Zhao, Shilu; Li, Xuan (Frontiers in Neurology, 2021)
Few studies have reported on simultaneous endovascular stenting for tandem posterior circulation (PC) stenoses and its long-term outcomes. Thus, our aim was to investigate the safety and efficacy of simultaneous stenting in patients with symptomatic tandem extra- and intracranial PC stenoses. From September 2014 to June 2018, 16 such patients with symptomatic stenoses who underwent simultaneous stent placement were analyzed. The primary outcome was occurrence of any stroke, TIA, or death within 30 days after the procedure. The secondary outcomes were technical success, clinical success, and the occurrence of in-stent restenosis ≥ 50% during follow-up. Technical success was defined as stent coverage of all tandem lesions and residual stenosis less than 30%. Clinical success was determined based on any occurrence of neurological events or death within 3 months after the procedure. All stents (19 intracranial and 14 extracranial) were placed with a technical success rate of 100%. One patient experienced a pontine ischemic stroke 2 days after the procedure and had recovered well at discharge. One patient experienced a minor complication of groin hematoma. The clinical success rate was 93.75% (15/16). During a median follow-up of 36.0 ± 11.0 months, 2 patients developed ISR ≥ 50% at the 1-year follow-up. None of the patients experienced stroke, TIA, or death after discharge during follow-up. Simultaneous stenting for symptomatic tandem extra- and intracranial PC stenoses is safe and feasible. Its impact on long-term stroke prevention is promising, and further study of a larger patient population is needed.